Analysis of IT Implementation in Computerized Accounting Systems in Digitalization Era - Ulfah, Rahmawati; Akhmad , Jamaah; Vina, Yunistiyani (UNKLAB Business School, 2026)
This study examines the implementation of Information Technology (IT) in computerized accounting systems and its transformative impact on accounting practices in the era of digitalization. Using a qualitative methodology through a systematic literature review, this research synthesizes findings from academic journals, books, and professional reports. The study reveals that cloud computing, Artificial Intelligence (AI), Big Data analytics, blockchain, and Internet of Things (IoT) technologies significantly enhance accuracy, efficiency, security, and decision-making in accounting. The findings further highlight challenges such as Impact of IT on Efficiency and Accuracy in Accounting, Ethical, Security, and Privacy Challenges, Strategic Transformation of the Accounting Profession, and Technological Integration and Organizational Performance. The study contributes to the growing body of literature by offering insights into technological integration and identifying future research opportunities to improve digital accounting practices.